Presence, Diversity, and Enrichment of Respiratory Reductive Dehalogenase and Non-respiratory Hydrolytic and Oxidative Dehalogenase Genes in Terrestrial Environments - Temme, Hanna R.; Carlson, Aaron; Novak, Paige J. (Frontiers in Microbiology, 2019)
Organohalide-respiring bacteria have been linked to the cycling and possible respiration of chlorinated natural organic matter (Cl-NOM) in uncontaminated soils and sediments. The importance of non-respiratory hydrolytic/oxidative dechlorination processes in the cycling of Cl-NOM in terrestrial soil and sediment, however, is still not understood. This research analyzes the dechlorination potential of terrestrial systems through analysis of the metagenomes of urban lake sediments and cultures enriched with Cl-NOM. Even with the variability in sample type and enrichment conditions, the potential to dechlorinate was universal, with reductive dehalogenase genes and hydrolytic or oxidative dehalogenase genes found in all samples analyzed. The reductive dehalogenase genes detected grouped taxonomically with those from organohalide-respiring bacteria with broad metabolic capabilities, as opposed to those that obligately respire organohalides. Furthermore, reductive dehalogenase genes and two haloacid dehalogenase genes increased in abundance when sediment was enriched with high concentrations of Cl-NOM. Our data suggests that both respiratory and non-respiratory dechlorination processes are important for Cl-NOM cycling, and that non-obligate organohalide-respiring bacteria are most likely involved in these processes.